Vulvar Lichen Sclerosus and Neoplastic Transformation: A Retrospective Study of 976 Cases. Issue 2 (April 2016) - Micheletti, Leonardo; Preti, Mario; Radici, Gianluigi; Boveri, Sara; Di Pumpo, Orazio; Privitera, Sebastiana S.; Ghiringhello, Bruno; Benedetto, Chiara
Abstract : Objective: The aim of the study was to estimate the neoplastic potential of vulvar lichen sclerosus (VLS). Materials and Methods: This was a retrospective study of 976 women with VLS. We recorded age at diagnosis of VLS, length of follow-up, and type of neoplasia, categorized as the following: (1) vulvar intraepithelial neoplasia (VIN), further subdivided in differentiated VIN (dVIN) and high-grade squamous intraepithelial lesion; (2) superficially invasive squamous cell carcinoma; and (3) frankly invasive squamous cell carcinoma. Neoplasia incidence risk, neoplasia incidence rate, and cumulative probability of progression to neoplasia according to the Kaplan-Meier method were estimated. Log-rank test was used to compare the progression-free survival curves by age at diagnosis of VLS. Results: The mean age at diagnosis of VLS was 60 (median = 60; range = 8–91) years. The mean length of follow-up was 52 (median = 21; range = 1–331) months. The following 34 patients developed a neoplasia: 8 VIN (4 dVIN, 4 high-grade squamous intraepithelial lesions), 6 keratinizing superficially invasive squamous cell carcinoma (5 with adjacent dVIN), and 20 keratinizing invasive squamous cell carcinoma (1 with adjacent dVIN). The neoplasia incidence risk was 3.5%. The neoplasia incidence rate was 8.1 per 1, 000 person-years. The cumulative probability of progression to neoplasia increased from 1.2% at 24 months to 36.8% at 300 months. The median progression-free survival was significantly shorter in older women (≥70 years) when compared with that in younger women ( p = .003). Conclusions: Vulvar lichen sclerosus has a nonnegligible risk of neoplastic transformation and requires a careful and lifelong follow-up in all patients, particularly in elderly women. Early clinical and histological detection of preinvasive lesions is essential to reduce the risk of vulvar cancer. Abstract : Vulvar lichen sclerosus has a nonnegligible risk of neoplastic transformation and requires a careful and lifelong follow-up in all patients, particularly in elderly women.